Managing brackish water to boost wheat and barley yield, water productivity, and maintain soil solute potential in the Ganges Delta - Khokan Kumer Sarker; Mohammed Mainuddin; Richard W. Bell; Edward G. Barrett-Lennard; Mark R. Glover; M. A. Hossain; S. S. A. Kamar; M. M. R. Sarker; Priya Lal Chandra Paul (Irrigation Science, 2026)

Skip Furrow Irrigation Increases Water Productivity, Maintains Yield and Decreases Soil Salinity for Sunflower in the Coastal Zone of the Ganges Delta - Khokan Kumer Sarker; Mohammed Mainuddin; Richard W. Bell; Manoj Kumar Nanda; Md. Mainul Islam; Md. Abdul Quddus; Mahanambroto Das; Md. Anower Hossain (Irrigation and Drainage, 2026)
Water‐saving irrigation is essential for crops in saline regions where freshwater resources are scarce. We tested furrow irrigation methods and planting techniques in terms of yield, water savings, water productivity (WP), soil salinity (EC e ) and soil water content (SWC) for sunflower in saline soils. Planting on the top of the ridge (T) or side slope on the ridge (S) were tested in factorial combination with (i) skip fixed furrow irrigation (SFFI), (ii) alternate furrow irrigation (AFI) or (iii) every furrow irrigation (EFI). The sunflower yield was significantly greater with the side of the ridge planting than on the top of the ridge. In consecutive years, sunflower yields were not significantly different among the furrow irrigation combinations with planting on side slopes of ridges. However, compared with the EFI, the SFFI and AFI saved 25 28% of the irrigation water and improved the WP. At a soil depth of 30 cm, the SFFI and AFI had significantly lower EC e values than did the EFI. Both skip furrow methods, with side slope planting on the ridge, offer water savings without sacrificing yields while decreasing the soil salinity and increasing the WP of sunflower in the water‐scarce, saline coastal regions of the Ganges Delta.

Earlier transplanting increases Boro rice yield and water productivity by minimizing exposure to high temperature and salinity in the coastal Ganges Delta - Priya Lal Chandra Paul; Richard W. Bell; Edward G. Barrett-Lennard; Mohammed Mainuddin; Donald S. Gaydon; Mark Glover; Marta Monjardino; Debjit Roy; Md. Belal Hossain; Md. Nazrul Islam; Sukamal Sarkar (Field Crops Research, 2026)

Developing scalable farm typologies to guide sustainable intensification in the fragile agroecosystems of the Indian Sundarbans - Kalyan Roy; Marta Monjardino; Mohammed Mainuddin; Sukamal Sarkar; Krishnendu Ray; Poulami Sen; Srijan Samanta; Akash Panda; Sanchayeeta Misra; Argha Ghosh; Esmat Ara Begum; Rupak Goswami (Agricultural Systems, 2026)

Achieving the once-unthinkable: Successful Rabi cropping via technology integration in coastal saline Bengal - Donald S. Gaydon; Sukamal Sarkar; Mohammed Mainuddin; Edward G. Barrett-Lennard; Richard W. Bell; Koushik Brahmachari; Md. Maniruzzaman; Buddheswar Maji; Md. Alimur Rahman; Md. Enamul Kabir; Md.Harunor. Rashid; Md. Shahidul Islam Khan; et al. (Agricultural Systems, 2026)

Climate-smart management of rice–pulse rotations in complex coastal saline ecosystems: an APSIM assessment - Sukamal Sarkar; Donald S. Gaydon; Mohammad Kamruzzaman; Mohammed Mainuddin; Anannya Dhar; Saikat Dey; Koushik Brahmachari (Agricultural Systems, 2025)

Land use change and soil salinization in the Sundarbans: a machine-learning based analysis of long-term transformation and future projections - Uttam Kumar Mandal; Amit Ghosh; Fazlul Karim; Sonali Mallick; Dibyendu Bikas Nayak; Rinchen Nopu Bhutia; Ajay Kumar Bhardwaj; Tashi D. Lama; Dhiman Burman; Priyanka Choudhury; Kshirendra Kumar Mahanta; Shishir Raut; et al. (Environmental Monitoring and Assessment, 2025)
Quantitative data on coastal land use changes are essential for effective resource management and sustainable development. In this study, we examined land use and land cover (LULC) changes, along with erosion and accretion, in the climate-sensitive Sundarbans of India using satellite imagery from 1973 to 2022. Over this period, approximately 478 km 2 of land was lost to erosion, while 408 km 2 were gained through accretion. Although single cropping remains the predominant land use system, the areas dedicated to settlements and aquaculture grew 7 times and 2.4 times, respectively. The double-cropped area expanded by 75.8%, while the mangrove area remained unchanged. Among all land use categories, single-cropped land was found to be the most vulnerable to loss. The soil salinity area of the arable land, calculated using the canopy response salinity index (CRSI) from satellite imagery, rose from 2246.2 km 2 to 2669 km 2 in the 30 years since 1989. Using a machine learning algorithm (cellular automata-artificial neural network (CA-ANN)), which incorporated both anthropogenic factors and projected temperature and rainfall data as explanatory variables, we estimated that by 2049, the settlement area will increase by 31.6%, aquaculture will expand by 30%, and vegetation cover will decrease by 12.6%, compared to 2019 levels. The LULC change trend and coastline dynamics are expected to further exacerbate land degradation as the model predicts an increase in soil salinity by 5% over the same period. The results help farmers and policymakers to develop effective land management plans to enhance community readiness and resilience against vulnerabilities.

A comprehensive review on the negative impacts on Sundarbans fisheries: Insights from the hydrological changes modulated by climate change and anthropogenic activities - Kizar Ahmed Sumon; Nayan Jyoti Roy Kanok; Md. Ashfaq Sadat; Mohammed Mainuddin; Shahriar M. Wahid; Fazlul Karim (Marine Pollution Bulletin, 2025)

Salinity dynamics in the Sundarbans of Bangladesh: influence of climate, freshwater inflow, and sea level changes - Shahriar Wahid; Mohammed Mainuddin; Francis Chiew; Fazlul Karim; Shaikh Nahiduzzaman; Rubayat Alam; Md. Raqubul Hasib (Environmental Monitoring and Assessment, 2025)
The Sundarbans mangrove ecosystem, the world’s largest contiguous mangrove forest, is under pressure from changing salinity due to climate change, reduced freshwater input from upstream rivers, and tidal dynamics in the Bay of Bengal. Despite its ecological and socio-economic significance, previous studies have not provided a comprehensive, location-specific assessment of salinity that explicitly links spatial heterogeneity with hydroclimatic drivers. This study synthesised and analysed the best available data in the Bangladesh Sundarbans over the 26 years to quantify the characteristics, trends, and interrelationships of these variables spatially and temporally. The results reveal that salinity has been consistently higher in the western part of the Sundarbans, and extreme salinity levels have increased since 2010. There has been a statistically significant decrease in the freshwater inflow from the Ganges through the Gorai River (at the Gorai railway bridge location) since the early 1980s, which has led to increased downstream salinity. Strong statistical correlations enabled robust predictions of salinity as a function of rainfall and temperature. A rising water level trend at Hiron Point is attributed to the rise in sea levels. The absence of long-term measurement data prevents the exploration of salinity dynamics in the numerous creeks that crisscross the mangrove ecosystem. It is crucial to establish continuous monitoring and assessment to better understand and manage the impacts of climate change and development on the Bangladesh Sundarbans and similar coastal ecosystems worldwide. Graphical abstract

Advancements in Extreme Precipitation Projections for South Asia: A Comparative Evaluation of CMIP5 and CMIP6 Models - Mohammad Kamruzzaman; Shahriar Wahid; Mohammed Mainuddin; Francis Chiew; Abu Reza Md Towfiqul Islam; Mohammed Magdy Hamed; Kelly R. Thorp; Shamsuddin Shahid (International Journal of Climatology, 2025)
Global climate models (GCMs) are essential for projecting future climate changes, yet their ability to accurately simulate extreme precipitation, particularly in South Asia, remains a major challenge. This study assessed the performance of GCMs from CMIP5 and CMIP6 in replicating 11 extreme precipitation indices, using ERA5 data from 1975 to 2005. The results revealed substantial variability across individual models, with CMIP6 generally outperforming CMIP5, though certain inconsistencies persisted. Both CMIP5 and CMIP6 multi‐model ensemble means (MMEs) exhibited higher root mean square error (RMSE) than the best individual models, highlighting the need for further improvements in model accuracy. On average, CMIP6 models achieved a Kling–Gupta efficiency (KGE) of 0.42, outperforming CMIP5's 0.38, and demonstrated better agreement in Taylor diagrams, with an average r 2 of 0.65 compared to 0.59 for CMIP5. CMIP6 also showed reduced uncertainty in interannual monthly precipitation variability projections. EC‐Earth3 (CMIP6) and EC‐Earth (CMIP5) consistently correlated well with various indices, while MIROC‐ESM was also a strong performer in both generations. The CMIP6 MME performed better overall, with a KGE of 0.48 and r 2 of 0.71, surpassing CMIP5 MME's 0.44 and 0.67. Future projections indicate significant changes in precipitation extremes under different emission scenarios for the 2040s and 2080s. While CMIP6 shows clear advancements over CMIP5, continued model refinement is essential to more accurately simulate extreme precipitation events.

Soil conductance classification for crop performance assessment using electromagnetic induction and geospatial techniques in coastal region of Indian Sundarbans - Manoj Kumar Nanda; Sukanta Kumar Sarangi; Mark Glover; Debolina Sarkar; Argha Ghosh; Momsona Mondal; Jorge Pena-Arancibia; Mohammed Mainuddin (Geoderma Regional, 2025)

Strategies of water resource utilization and agricultural water management in the coastal saline zone of Bangladesh - Md. Belal Hossain; Debjit Roy; Priya Lal Chandra Paul; Mst. Shetara Yesmin; Palash Kumar Kundu; Mohammad Rezoan Bin Hafiz Pranto; Md Aklimuzzaman; Mousumi Paul; Md. Maniruzzaman; Mohammed Mainuddin (Irrigation and Drainage, 2025)
Access to irrigation water is pivotal for dry season crops in the coastal saline regions of Bangladesh. This research investigates strategic measures aimed at ensuring water availability for polder agricultural purposes in the dry season. This study was performed from 2017 to 2022 to assess the water availability inside polders # 30 and # 31 in Khulna region of the south‐western coastal zone of Bangladesh. Our methodology encompassed diverse approaches: identifying optimal water sources, capturing low‐salinity water for agriculture, implementing crop–soil–water management to enhance cropping intensity, employing irrigation modelling for effective crop planning, utilizing GIS techniques to estimate water storage and conducting impact analysis using satellite images. Irrigation by trapped river water increased the yield of different crops by 13–56% compared with that of farmer‐managed plots. Polders # 30 and # 31 currently have approximately 136 and 190 km of good canals, which store 334 and 502 ha‐m of water, respectively, during the dry period. With the existing stored fresh water, a maximum of 6,680 ha and 10,040 ha of watermelon and a minimum of 334 and 502 ha of boro rice cultivation were possible in polders # 30 and # 31, respectively. However, the excavation of poor and dead canals could increase freshwater storage and crop coverage. The image analysis of polder #31 revealed an increase in crop coverage of 238% from 2017 to 2022, which might be attributed to the introduction of advanced water management technologies and salt‐tolerant cultivars as well as holistic extension approaches by different government organizations (GOs), non‐governmental organizations (NGOs) and farmers. This study will assist in formulating pathways for polder‐scale water management and cropping intensification in coastal saline zones.

Greenhouse gas emissions from dry season rice irrigation in Bangladesh - Md. Maniruzzaman; Jatish Chandra Biswas; Md. Belal Hossain; Mohammed Mainuddin; Debjit Roy; Mst. Shetara Yesmin; Palash Kumar Kundu; Md. Mozammel Haque (Mitigation and Adaptation Strategies for Global Change, 2025)
Pumping groundwater for irrigation in Bangladesh is a major energy-consuming process and mostly depends on diesel fuel, which is related to greenhouse gas (GHG) emissions. But that issue has not yet been addressed in Bangladesh. `In this study, we have estimated GHG emissions for dry season (DS) irrigated rice considering all irrigation devices with their lifting heads, area coverage, and water sources (surface and groundwater) and power sources (diesel and electricity) during 2019–2020. GHG emissions varied with locations, sources of irrigation, fuel and water sources used. Irrigation water driven GHG emission in Bangladesh is about 2.27 million tons (Mt) CO 2 e DS −1 , which is about only 4% of agricultural sector GHG emission. Groundwater pumps contributed the lion shares (2.04 Mt CO 2 e DS −1 ), and surface water pumps contributed only 0.23 Mt CO 2 e DS −1 . Based on the GHG emissions, Rajshahi Division is the main hotspot followed by Rangpur and Mymensingh Divisions, because of intensive groundwater used in these areas. Current deep tubewells (DTWs), shallow tubewells (STWs) and low lift pumps (LLPs) area coverage is about 19.2%, 56.8% and 24.0% of the total cultivable areas of the country; but it contributes about 49.1%, 40.6% and 10.3% of emitted GHG, respectively. The results revealed that withdrawal of groundwater is an important source of GHG emission. Therefore, expansion of surface water irrigation facilities with the adoption of different improved distribution systems, water and energy saving technologies like alternate wetting and drying practices, conservation agriculture along with water use-efficient varieties for rice cultivation can be promoted for reducing GHG emission.

Assessment of inundation extent due to super cyclones Amphan and Yaas using Sentinel-1 SAR imagery in Google Earth Engine - Momsona Mondal; Manoj Kumar Nanda; Jorge Luis Peña-Arancibia; Debolina Sarkar; Argha Ghosh; Rupak Goswami; Asis Mukherjee; Abhijit Saha; Koushik Brahmachari; Sukamal Sarkar; Mohammed Mainuddin (Theoretical and Applied Climatology, 2024)

Kharif rice growth and area monitoring in Gosaba CD block of Indian Sundarbans region using multi-temporal dual-pol SAR data - Argha Ghosh; Manoj Kumar Nanda; Debolina Sarkar; Sukamal Sarkar; Koushik Brahmachari; Mohammed Mainuddin (Environment, Development and Sustainability, 2023)

Modelling the impacts of climate change and management options on sustainable groundwater use in an irrigated agriculture landscape - Fazlul Karim; Md Tohidul Islam; Mohammed Mainuddin; Sreekanth Janardhanan; Md Monirul Islam; Md Sohel Masud; Md Rezanur Rahman; John M. Kirby (Groundwater for Sustainable Development, 2023)

Assessing the cropping intensity dynamics of the Gosaba CD block of Indian Sundarbans using satellite-based remote sensing - Argha Ghosh; Manoj Kumar Nanda; Debolina Sarkar; Sukamal Sarkar; Koushik Brahmachari; Mohammed Mainuddin (Environment, Development and Sustainability, 2023)

Relative performance of CMIP5 and CMIP6 models in simulating rainfall in Peninsular Malaysia - Sahar Hadi Pour; Shamsuddin Shahid; Mohammed Mainuddin (Theoretical and Applied Climatology, 2022)

An intra-household analysis of farmers’ perceptions of and adaptation to climate change impacts: empirical evidence from drought prone zones of Bangladesh - A. K. M. Abdullah Al-Amin; Tahmina Akhter; Abu Hayat Md. Saiful Islam; Hasneen Jahan; M. J. Hossain; Md. Masudul Haque Prodhan; Mohammed Mainuddin; Mac Kirby (Climatic Change, 2019)

National food security in Bangladesh to 2050 - Mohammed Mainuddin; Mac Kirby (Food Security, 2015)

Spatial and temporal variations of, and the impact of climate change on, the dry season crop irrigation requirements in Bangladesh - Mohammed Mainuddin; Mac Kirby; Rehab Ahmad Raihan Chowdhury; Sardar M. Shah-Newaz (Irrigation Science, 2015)

Impact of climate change on rainfed rice and options for adaptation in the lower Mekong Basin - Mohammed Mainuddin; Mac Kirby; Chu Thai Hoanh (Natural Hazards, 2013)

Adaptation to climate change for food security in the lower Mekong Basin - Mohammed Mainuddin; Mac Kirby; Chu Thai Hoanh (Food Security, 2011)

Agricultural productivity in the lower Mekong Basin: trends and future prospects for food security - Mohammed Mainuddin; Mac Kirby (Food Security, 2009)